HOW TO DESCRIBE THE RESULTS OF OBSERVATIONAL EPIDEMIOLOGICAL STUDIES - S. A. Shal'nova; A. D. Deev (Рациональная фармакотерапия в кардиологии, 2016)
Principles and fundamentals of proper presentation of observational epidemiological study results are focused. Principles of observational study publication developed by expert epidemiologists (STROBE statement) are explained in detail.